PENGEMBANGAN MASYARAKAT (Sebuah Kerangka Koseptual) - Suryadi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2018)
ABSTRACTÂ Community is a physical place, but it also can be defined as people who live in the same location, share common interests, jointly own or participate in something, share common characteristics, or have mutual relations. Development relates to realizing potential, growth or expansion of something, or making something more effective. Put together simply, community development is the act of growing, expanding or making more effective groups of people who have mutual interests. Many theories and strategies have been developed to attain community goals. There are also administrative and managerial aspects in designing approach in community development programs.Key words: community, development, strategies